Re-framing Corporate Narratives: A Conceptual Analysis of Media Relations Strategies in Antam’s 109-Ton Gold Certification Crisis - Jestiawati; Asih Febriani; Yesi Permatasari; Pramudya Ibnu Subrata (CITACONOMIA, 2026)
This conceptual article examines the strategic role of media relations in navigating reputational crises triggered by digital misinformation, using the case of PT Aneka Tambang Tbk’s gold certification controversy (2024–2026). The study identifies a significant narrative distortion where administrative procedural issues were misconstrued by public perception as product integrity failures, amplified by social media algorithms. Employing a qualitative descriptive method and Situational Crisis Communication Theory (SCCT), this research analyzes how the organization transitioned from rigid legalistic rhetoric to an adaptive